Twentieth-century Pittsburgh. the post-steel era - Lubove, Roy (University of Pittsburgh Press, 1996)
This volume traces the major decisions, events, programs, and personalities that transformed the city of Pittsburgh during its urban renewal project, which began in 1977. Roy Lubove demonstrates how the city showed united determination to attract high technology companies in an attempt to reverse the economic fallout from the decline of the local steel industry. Lubove also separates the successes from the failures, the good intentions from the actual results.